Love thy neighbor (or not): Regionalism and support for the use of offshore wind energy by others. (August 2022) - Bidwell, David; Firestone, Jeremy; Ferguson, Michael D.
Abstract: Distributive fairness influences public acceptance of renewable energy technologies. Concerns about distributive fairness contribute to opposition to export of electricity and public preferences for electricity to be consumed near its production. Distributional issues are relevant to offshore wind energy development, where the coastal communities nearest to the developments may see none of the jobs, economic development, or profits associated with development, with undersea cables often delivering the electricity to faraway places. In a survey of coastal residents in the northeast United States, we find differences in support for use of offshore wind energy in their own state. Support for electricity use by other states, however, reveals the effects of subnational regionalism. Residents of Rhode Island prefer the use of electricity produced off their shores by the state of Massachusetts over New York; residents of New Hampshire prefer for Maine to consume energy over Massachusetts. These findings portend conflicts over the transmission of electricity as offshore wind energy development expands in U.S. and has implications for all renewable energy transmission that crosses regional boundaries.